Poly Implant Prothèse Asymmetrical Anatomical Breast Implants: A Product Recall Study. Issue 1 (January 2015) - De Lorenzi, Francesca; Gazzola, Riccardo; Sangalli, Claudia; Villa, Oriana; Marchetti, Miriam; Monturano, Massimo; Petit, Jean Yves; Garusi, Cristina; Martella, Stefano; Manconi, Andrea; Barbieri, Benedetta; Gottardi, Alessandra; et al.
Abstract : Background: In 2010 high rupture rates were unexpectedly found among prostheses produced by the French manufacturer Poly Implant Prothèse. Since then, several studies have been performed concerning the round implants, but there are still few data available on anatomical implants. Methods: From 2003 to 2006 Poly Implant Prothèse implants were employed at the authors' institute for immediate or delayed reconstruction after mastectomy. All implants were anatomical and asymmetrical. In November of 2010, the authors began offering free consultation with a plastic surgeon and radiologist. Demographic data, type of reconstruction, implant lifespan, indications for implant removal, and rupture rate were recorded. Results: A total of 578 women underwent postmastectomy immediate or delayed reconstruction with 658 Poly Implant Prothèse implants from 2003 to 2006 at the authors' institute. The authors explanted 409 of 443 prostheses, and 34 were explanted at other centers. Eighty-nine patients died and 120 are alive with the implants in place. The mean implant lifespan was 57.5 months, 76 ruptured implants were explanted (18.5 percent), and in 22 cases (5.4 percent), leakage of silicone gel was detected. Conclusions: Poly Implant Prothèse implant failure is to be ascribed to shell structure, although the primary safety issue concerned the gel (an industrial-grade and low-cohesive silicone). These issues produce the known rupture rates in the manufacturer's round implants. The authors' use of only anatomical and asymmetrical implants, with their more cohesive silicone gel and more rigid shell allowing a stable form and projection along with a natural feel and touch, probably reduces the rupture rate and silicone spread, although these events remain unacceptably high compared with similar products of other brands. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.